(3GdCHjGJ GdMSGf GdeLQOI ef hajGJ GdCYjGfs
(3ChdgG (B:s
(3hHYO(B: (3abO CeQfj ef CeQg eWGY Cf CLeY eG ChQOg bGVj GdbVGI GHf NdcGf aj JGQjNg GdoeSei HhajGJ GdCYjGf ef GdCHjGJ GdeTjOI GdCQcGf aCLHJg eeJKdkG dCeQg s
(3BNQgG (B:s
(3eGMc LdOc eKd XaQc bJhd CfJ LejY CeQc aEPG bUOJ dMGLI aCbUO deYJQa HbOQc s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B3 s
(3eUOQ GbJfGA GdCUd (B:s
(3WgQGf (B- (3SHgSdGQ (B(1102) s
Keywords: (3GdCOHs